Evaluasi Penyelenggaraan Sekolah Bertaraf Internasional (SBI) di Sekolah Dasar (SD), Sekolah Menengah Pertama (SMP), Sekolah Menengah Atas (SMA), dan Sekolah Menengah Kejuruan (SMK) - Idris HM Noor (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2011)
The implementation of pilot standard of international school (pre SIS) is one of the government’s efforts to improve educational quality in order to be able to compete with other countries. Since the establishment of the pre SIS in 2006, they have not been evaluated comprehensively yet. Therefore, it is important to evaluate the student’s enrolment, academic achievement, finance and budgetting, and management. Research method used is mixed quantitative and qualitative method. Samples are 4575910 respondents chosen purposively. They are school committee, school principals, teachers of pre SIS and regular classe. They are English, mahtematics, and science teachers, students, and students’ parents association. The English proficiency of school principals is at the novice level (10-250 TOEIC scores). Teachers’ academic competence of pre SIS and regular classes is relatively equal. The competence of biology and physics teachers of pre SIS in SSS is lower than those in the regular classes. The use of budget and finance is not transparent. Recommendation, it is important to improve teachers’ academic qualification and their competence and a rigid financial and budgeting management guide. ABSTRAKPenyelenggaraan RSBI merupakan salah satu usaha pemerintah untuk meningkatkan mutu pendidikan agar mampu bersaing dengan negara lain. Sejak diselenggarakan tahun 2006, RSBI belum pernah dievaluasi secara komprehensif. Oleh karena itu, perlu dievaluasi PPDB, prestasi, pengelolaan pendanaan, dan sistem tata kelola dan akuntabilitas penyelenggaraannya. Penelitian menggunakan metode campuran kuantitatif dan kualitatif. Sampel sebanyak 4575910 yang diambil secara purposive. Responden: komite sekolah, kepala sekolah, guru bahasa Inggris, matematika, dan IPA yang mengajar di kelas RSBI dan kelas reguler. Temuan: Kemampuan bahasa Inggris pendidik dan tenaga kependidikan RSBI di semua tingkat masih level novice (skor TOEIC 10-250). Kemampuan guru bahasa Inggris kelas RSBI dan kelas reguler relatif sama. Di SD dan SMP, kemampuan siswa dan guru RSBI sedikit lebih tinggi daripada kelas regular. Kemampuan guru Biologi dan Fisika kelas RSBI di SMA lebih rendah daripada guru kelas reguler. Penggunaan dana kurang transparan. Rekomendasi, perlu peningkatan kualifikasi dan kompetensi akademik guru dan perlu disusun panduan pengelolaan pendanaan yang lebih rinci.